Genome-wide alternative polyadenylation dynamics underlying plant growth retardant-induced dwarfing of pomegranate - Xia, Xinhui; Fan, Minhong; Liu, Yuqi; Chang, Xinyue; Wang, Jingting; Qian, Jingjing; Yang, Yuchen (Frontiers in Plant Science, 2023)
Dwarfed stature is a desired agronomic trait for pomegranate (Punica granatum L.), its advantages in cost saving and yield promoting. A comprehensive understanding of regulatory mechanisms underlying the growth repression would provide a genetic foundation to molecular-assisted dwarfing cultivation of pomegranate. Our previous study induced dwarfed pomegranate seedlings via exogenous application of plant growth retardants (PGRs) and highlighted the important roles of differential expression of plant growth-related genes in eliciting the dwarfed phenotype of pomegranate. Alternative polyadenylation (APA) is an important post-transcriptional mechanism and has been demonstrated to act as a key regulator in plant growth and development. However, no attentions have been paid to the role of APA in PGR-induced dwarfing in pomegranate. In this study, we characterized and compared APA-mediated regulation events underlying PGR-induced treatments and normal growth condition. Genome-wide alterations in the usage of poly(A) sites were elicited by PGR treatments, and these changes were involved in modulating the growth and development of pomegranate seedlings. Importantly, ample specificities were observed in APA dynamics among the different PGR treatments, which mirrors their distinct natures. Despite of the asynchrony between APA events and differential gene expression, APA was found to regulate transcriptome via influencing microRNA (miRNA)-mediated mRNA cleavage or translation inhibition. A global preference for lengthening of 3' untranslated regions (3' UTRs) was observed under PGR treatments, which was likely to host more miRNA target sites in 3' UTRs and thus suppress the expression of the corresponding genes, especially those associated with developmental growth, lateral root branching and maintenance of shoot apical meristem. Together, these results highlighted the key role of APA-mediated regulations in fine-tuning PGR-induced dwarfed stature of pomegranate, which provide new insights into the genetic basis underlying the growth and development of pomegranate.